Ceramic repair without hydrofluoric acid - Bergoli, César Dalmolin; de Carvalho, Rodrigo Furtado [UNESP]; Luz, Julio Nogueira [UNESP]; Luz, Murilo Souza; Meincke, Débora Könzgen; Saavedra, Guilherme de Siqueira [UNESP] (My University, 2016)
Purpose: To evaluate the bond strength between composite resin and feldspathic ceramic following repair protocols with and without hydrofluoric acid and aging by thermocycling. Materials and Methods: Forty-eight glass feldspathic ceramic blocks (8 x 8 x 6 mm) were divided into three groups on the basis of their surface repair treatment: 1. 10% hydrofluoric acid + Signum Ceramic Primer I + Signum Ceramic Primer II (control group); 2. abrasive rubber tips + Signum Ceramic Primer I + Signum Ceramic Primer II (test group); 3. Signum Ceramic Primer I + Signum Ceramic Primer II (negative control group). The treated surface of each block was built up with composite and then sectioned to produce nontrimmed bars (adhesive area = 1 mm2). Half of the bars from each group were aged by 6000 cycles of 30-s immersions in water baths at 5°C and 55°C, with a transfer time of 2 s. The other bars were immediately subjected to microtensile bond strength testing. The mean bond strength for each block was then recorded and submitted to two-way ANOVA and Tukey's test (α = 0.05). Results: The aging protocol influenced the bond strength values of all groups (p = 0.000). The non-aged groups submitted to surface treatment protocols 1 (13.1 ± 2.5 MPa) and 2 (11.5 ± 5.1 MPa) presented the highest bond strength values. Conclusions: The interface bond strength of all groups was susceptible to aging. Surface treatment protocol 2, with abrasive rubber tips and no hydrofluoric acid, appeared to be the most promising option, as the resulting bond strength values were similar to those of the control group.
Keywords: Ceramic surface treatment; Feldspathic repair; Glass ceramic